Evaluation of water resources in a high-mountain basin in Serra da Estrela, Central Portugal, using a semi-distributed hydrological model - Marques, Jorge Manuel Espinha (2018)
Submitted by Geopark Estrela (geopark.estrela@ubi.pt) on 2018-11-21T17:06:43Z No. of bitstreams: 1 2010 EES Serra da Estrela Espinha Marques_final.pdf: 1526840 bytes, checksum: 24cb50d1507e36e91f01c6da4f0e5eb6 (MD5)